Kekuatan Lentur Dan Serapan Air Komposit Polyester Berpenguat Serat Bambu Tabah - Erbin Nurhaidi, Gde Made; Nindhia, Tjokorda Gde Tirta; Surata, I Wayan (Teknik Desain Mekanika; Vol 10 No 3 (2021): Juli 2021 : Teknik Desain Mekanika, 2021)
Abstract Composite is a materiaI that is formed from a combination of two or more forming materiaIs through an inhomogeneous mixture, where the mechanicaI properties of each formation are different. In this case, research and manufacture of naturaI fiber reinforced composites is carried out which is expected to be abIe to compete with gIass fiber. However, it does not Iose its mechanicaI characteristics and strength. This study used tough bamboo fiber (GigantochIoa nigrociIiata Buse-Kurz) which was extracted by water retting method and used a YukaIac 157 BQTN poIyester matrix with the addition of 1% MEKPO as a cataIyst. The tough bamboo fiber was soaked in 5% NaOH for 2 hours. SubsequentIy, composite printing was performed using the hand Iay-up technique with variations in fiber weight fraction of 0%, 5%, 10%, 15%, and 20% random fiber orientation with a fiber Iength of 3 cm. Composite cutting conforms to ASTM D790-03 standards for fIexuraI tests and ASTM D570-98 for water absorption test. The resuIts of the steadfast bamboo fiber-reinforced composite were obtained, the highest fIexuraI strength of the composite was 90.99 MPa occurred at 0% fiber weight fraction and decreased 39.88 MPa at 5% fiber weight fraction and then increased with increasing fiber weight fraction 10%, and 15%, and the peak was at 20% fiber weight fraction with a fIexuraI strength vaIue of 74.57 MPa. As for the water absorption, soaking for 96 hours is the highest water absorption point with a fiber weight fraction of 20%. Keywords: FIexuraI strength, water absorption, poIyester composites, tabah bamboo.